Peripheral Airway Dysfunction Assessed by Impulse Oscillometry in School-Aged Children Born Preterm: A Cross-Sectional Comparative Study - Nezihe Koker Ozer; Ercan Yılmaz; Hatice Turgut; Erdem Topal; Ramazan Ozdemir; Recep Gunakın; Mehmet Aslan (Journal of Clinical Medicine, 2026)
Background: Preterm birth may result in persistent alterations in peripheral airway development. We aimed to compare impulse oscillometry (IOS) parameters between school-aged children born preterm and healthy term-born controls and to investigate factors associated with peripheral airway dysfunction. Methods: This cross-sectional comparative study included 46 children born at ≤32 weeks of gestation and 40 independently recruited healthy term-born controls. IOS parameters, including R5, R20, R5–R20, X5, X20, AX, and Fres, were assessed. Multivariable linear regression was used to evaluate whether between-group differences persisted after adjustment for anthropometric measures. Results: Children born preterm had significantly higher R5 (0.75 vs. 0.48 kPa·s/L), R5–R20 (0.37 vs. 0.19 kPa·s/L), and AX (2.93 vs. 1.41 kPa/L) than controls (all p = 0.001), whereas R20, X5, X20, and Fres did not differ significantly. R5–R20 was the most frequently abnormal IOS parameter in the preterm group (34.8%). After adjustment for age, height z-score, and weight z-score, prematurity remained significantly associated with higher R5 (p = 0.005), R5–R20 (p < 0.001), and AX (p = 0.002). No significant associations were identified between R5–R20 and gestational age, bronchopulmonary dysplasia, mechanical ventilation, or other evaluated neonatal characteristics. Conclusions: School-aged children born preterm exhibit persistent differences in peripheral airway mechanics that are not explained by anthropometric differences. IOS may provide a useful complementary tool for long-term respiratory assessment after preterm birth.